Trials on Raising Teak (Tectona grandis) Planting Stock in Root Trainers - Khedkar, M. H.; Subramanian, K. (Indian Forester, 1997)
The Teak planting stock is usually raised in raised beds or poly bags. The first ever attempt in India to raise Teak planting stock in Root trainers is described. The trial scale Root trainer seedlings raised in Root trainers have given better development of biologically desirable lateral roots. Observation on multiple tap roots in the Root trainer planting stock is reported. The comparative growth performanee of plants of 75 days old Root trainer planting stock origin with the one year old Teak stump origin in the out planting site is recorded. The Root trainer plants are sturdier, healthier and they are putting up better collar girth in comparison to stump origin plants. The need to standardise the pregermination of Teak seeds and the Teak Root trainer nursery technology are indicated. The advantages of the Teak Root trainer seedlings over Teak stumps are narrated.